2021
DOI: 10.1371/journal.pone.0261554
|View full text |Cite
|
Sign up to set email alerts
|

Use of spineless cactus associated with legume hay in the feedlot-finishing of lambs in semi-arid regions

Abstract: The objective of this study were to examine the effects of diets containing spineless cactus associated with hays of different legume species [gliricidia (Gliricidia sepium), “catingueira” (Caesalpinia bracteosa), “sabiá” (Mimosa caesalpiniifolia Benth) and “catanduva” (Piptadenia moniliformis Benth)] on the intake, digestibility, performance and carcass traits of lambs. Twenty-four ½ Santa Inês × ½ Soinga lambs with an average body weight of 21.4 ± 2.53 kg were distributed into four treatments in a completely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…The effectiveness of fiber was broken by the particle size of the roughage, so the intestinal passage rate could not reveal possible interactions between the roughages used (Tifton 85 or Cratylia hay). The digestibility coefficient values found in this study are similar to those described by other authors [29], which included shrub hay and tree legume species as roughage sources in the total diet of feedlot lambs.…”
Section: Plos Onesupporting
confidence: 90%
“…The effectiveness of fiber was broken by the particle size of the roughage, so the intestinal passage rate could not reveal possible interactions between the roughages used (Tifton 85 or Cratylia hay). The digestibility coefficient values found in this study are similar to those described by other authors [29], which included shrub hay and tree legume species as roughage sources in the total diet of feedlot lambs.…”
Section: Plos Onesupporting
confidence: 90%
“…The weight and yield of carcasses are significant determinants of commercial value with better returns ( 75 ). The mean tissue content of the leg showed that the muscles had the greatest contribution (66.70%), followed by bone (18.89%) and fat (10.09%) ( 76 ). Bautista-Díaz et al ( 77 ) reported that bones made up 1.46 ± 0.27 kg of suckling lambs.…”
Section: Discussionmentioning
confidence: 99%
“…On account of the weights of primal cuts recorded in this study, the carcasses provided reasonable cut yields when the leg, loin, and shoulder were considered ( 78 ). Da Trindade Silva et al ( 76 ) reported that these are responsible for an estimated 60% of the entire yield of cuts. Results generated from this study with other carcass traits could therefore be useful when making decisions regarding the selection and the most appropriate husbandry system to employ.…”
Section: Discussionmentioning
confidence: 99%
“…The forage cactus plants are widely used in arid and semi-arid regions, since, due to their phenotypic plasticity, they are more efficient in water use in scenarios with low precipitation rates (Silva et al, 2021;Pereira et al, 2021;Lima et al, 2023). Furthermore, according to Edvan et al (2020) plants of Opuntia stricta cv.…”
Section: Introductionmentioning
confidence: 99%